Selective Laser Melting of the Porous Ta Scaffold with Mg-Doped Calcium Phosphate Coating for Orthopedic Applications - Xu, Jianfeng; Wu, Di; Ge, Bing; Li, Maoyuan; Yu, Haiyu; Cao, Fang; Wang, Weidan; Zhang, Qing; Yi, Pinqiao; Wang, Haiyao; Song, Liqun; Liu, Lingpeng; et al. (ACS biomaterials science & engineering, 2024)
Addressing the repair of large-scale bone defects has become a hot research topic within the field of orthopedics. This study assessed the feasibility and effectiveness of using porous tantalum scaffolds to treat such defects. These scaffolds, manufactured using the selective laser melting (SLM) technology, possessed biomechanical properties compatible with natural bone tissue. To enhance the osteogenesis bioactivity of these porous Ta scaffolds, we applied calcium phosphate (CaP) and magnesium-doped calcium phosphate (Mg-CaP) coatings to the surface of SLM Ta scaffolds through a hydrothermal method. These degradable coatings released calcium and magnesium ions, demonstrating osteogenic bioactivity. Experimental results indicated that the Mg-CaP group exhibited biocompatibility comparable to that of the Ta group in vivo and in vitro. In terms of osteogenesis, both the CaP group and the Mg-CaP group showed improved outcomes compared to the control group, with the Mg-CaP group demonstrating superior performance. Therefore, both CaP and magnesium-CaP coatings can significantly enhance the osseointegration of three-dimensional-printed porous Ta, thereby increasing the surface bioactivity. Overall, the present study introduces an innovative approach for the biofunctionalization of SLM porous Ta, aiming to enhance its suitability as a bone implant material.